Numerical investigation of coupled density-driven flow and hydrochemical processes in coastal aquifers influenced by storm surges - Sun, Qiming; Gao, Maosheng; Wen, Zhang; Hou, Guohua; Dang, Xianzhang; Zhao, Guangming (Continental shelf research, 2023)
Storm surges can result in significant damage to coastal aquifers. Studies have investigated groundwater salinization caused by storm surge inundation. However, the phenomenon of evaporation-driven mineral precipitation in saltwater lakes has not received much attention in the literature. To address this gap, this study simulated the impact of saltwater lakes formed after a storm surge on coastal aquifers by coupling the PHREEQC and SEAWAT models. Six scenarios were considered, with varying lake depth, area, evaporation rate and vertical hydraulic conductivity of lakebed. The results indicate that the total dissolved solids (TDS) and water level of saltwater lake are subject to constant changes due to evaporation. Scenario 2, with the smallest lake area exhibited the least susceptibility to evaporation, with a maximum TDS concentration in the lake of ∼86 g/L, and only dolomite and calcite reached saturation. However, infiltration of saline water into the aquifer was higher than for the other scenarios. A comparing of scenarios with different vertical hydraulic conductivities of lakebed (scenarios 5 and 6 have conductivities that are 0.1 × and 0.01 × that of scenario 1, respectively) shows that a smaller vertical hydraulic conductivity leads to less saline infiltration into the aquifer, but a greater amount of salt precipitates (precipitation ratios of 1.03%, 1.92%, and 5.73% for scenario 1, 5 and 6, respectively). The results of scenario 4, which has double the evaporation rate of the other scenarios, indicate that evaporation leads to significantly greater salt precipitation and a corresponding decrease in the amount of salt that enters the aquifer. The results of secondary salinization indicate that salt precipitated on the surface may infiltrate the aquifer through rainfall dissolution, causing groundwater to become saline again. These findings emphasize the importance of accounting for the impact of evaporation on saltwater lake dynamics and coastal groundwater salinization in future studies. •Investigating the effect of evaporation on groundwater salinization after storm surges.•Modeling salt precipitation in the SL due to evaporation by coupling SEAWAT and PHREEQC.•Simulating the secondary salinization due to dissolution of precipitated salts during rainfall recharge.